Relationship Between Leg Muscle Power, Arm Muscle Power, and Anthropometry with The Speed of The Ball Resulting from an Open Spike in Athletes of The Sumedang Integrated Indonesian Generation School Volleyball Team - Resik Citra Gemilang; Tono Haryono; Finaldhi Palgunadhi (Universitas Negeri Semarang, 2025)
This study aims to analyze the relationship between leg muscle power, arm muscle power, and anthropometry with the speed of the ball resulting from an open spike in athletes from the Sumedang Integrated Indonesian Volleyball Generation School. The study used a quantitative approach with a correlational method. The sample consisted of 21 athletes, with leg muscle power measured using the Vertical Jump Test, arm muscle power measured using an 8-second push-up test, and anthropometric data obtained through Karada Scan. The speed of the open spike ball was measured using a Speed Radar Gun. The data were analyzed using descriptive statistics, normality tests, Pearson or Spearman correlations, and multiple regression with a significance level of p < 0.05. The results showed that arm muscle power, height, weight, and body muscle mass were significantly related to ball speed, while several other variables such as leg power (Spearman), leg muscle mass, and BMI showed no significant relationship. Multiple regression analysis shows that the three independent variables simultaneously contribute 45.4% to ball speed. This finding confirms that spike performance is the result of an interaction between muscle strength and anthropometric characteristics. This study recommends a training program that focuses on strengthening the arm muscles, developing core strength, and managing body composition to improve spike speed in volleyball athletes.